Customer satisfaction towards services provided by Tenaga Nasional Berhad in Melaka Tengah, Melaka / Ahmad Bahtiar Mohd Bashir - Mohd Bashir, Ahmad Bahtiar (Faculty of Business and Management, 2006)
The purpose of this research is to study the customer's satisfaction towards the services provided by Tenaga Nasional Berhad in Melaka Tengah, Melaka and the relationship between counter service, service quality, and physical facilities with customer's satisfaction. Moreover, this study will examine and measure the level of customer's satisfaction and the relationships of the items that will influence their satisfaction with the service provided to them in order to enhance and gain more satisfaction among the customers. The findings showed that most of the customers were satisfied with the service provided to them and physical facilities have a strong relationship, while counter service have moderate relationship and service quality have weak relationship with customer's satisfaction. The researcher is also able to give some recommendations and suggestion on how to improve and increase customer's satisfaction of the customers after the analysis, findings and interpretation. In this study, we used interviews and questionnaire techniques for data collection. Based on frequency, cross tabulation and correlation, a clear findings and result is observed.